Attitude and satisfaction in green supply chain management Using eco-friendly packaging instead of single-use plastic packaging that influences food and beverage purchasing decisions in Bangkok - Siripany, Suratsawadee; Suesawadwanit, Piyamas (Journal of Management Science Nakhon Pathom Rajabhat University, 2023)
This research study aims to study Attitude and satisfaction in green supply chain management Using eco-friendly packaging instead of single-use plastic packaging that influences food and beverage purchasing decisions in Bangkok. A questionnaire was used to collect data from a sample of 400 people living in Bangkok by multi-stage random sampling. randomly by means of drawing lots and specific random methods Data were analyzed using statistics, percentage, mean, standard deviation, independent sample T-Test, One-Way ANOVA and multiple regression analysis by Enter method. Findings: 1. Level of attitude and satisfaction in green supply chain management The use of environmentally friendly packaging instead of single-use plastic packaging influences food and beverage purchase decisions in Bangkok. Overall and in each aspect, opinions were at a high level. Sorted in the following order: Satisfaction Purchasing decisions and attitudes toward green supply chain management 2. Attitudes toward green supply chain management on purchasing decisions of food and beverages using environmentally friendly packaging in Bangkok Statistically significant at the 0.05 level. The equation has the predictive power of 70.50 percent. The multiple regression analysis equation is Ŷ= 1.27 - 0.14X1 + 0.16X2 + 0.11X3 + 0.10X4 + 0.16X5 3. Satisfaction with food and beverage packaging using environmentally friendly packaging instead of single-use plastic packaging influencing food and beverage purchase decisions in Bangkok Statistically significant at the 0.05 level, the equation has a predictive power of 64.00 percent. The multiple regression analysis equation is Ŷ = 1.16 - 0.27X6 + 0.09X7 + 0.07X8 + 0.06X9 + 0.06X10 + 0.09X11 + 0.02X12 + 0.04X13 Article history: Received 2 November 2022 Revised 17 December 2022 Accepted 19 December 2022 SIMILARITY INDEX = 0.65 %